Improvement of Seedling Vigour by Chemopriming in Cashew - MEERA MANJUSHA AV; PK RETHEESH (Seed Research, 2026)
Cashew (Anacardium occidentale L.), is mainly propagated through soft wood grafting. Success ofgrafting and health of the graft is profoundly influenced by the vigour of root stock. In many crops, seed priminghas been reported as an effective technique to produce vigorous seedlings. Hence a study was conducted atKerala Agricultural University Regional Agricultural Research Station (North zone), Pilicode, to know the influenceof different seed priming agents on growth and vigour of the rootstock seedlings of cashew. Seeds of the cashewvariety: Priyanka, which is popular in the region, was used for raising the root stock seedlings. There were significantdifferences on the percentage of germination of seeds among the treatments. While the percentage of germinationwas highest for the seeds primed with KCl 0.5%, that was lowest for the seeds primed with urea 5% and 10%.Germination rate was highest for KNO3 3%. Differential responses to treatments were noticed as days progressed.At 15 days after sowing (DAS), seed vigour index (SVI) was highest with KNO3 1% and 3% treatments, though theseedling length, girth and number of leaves did not vary significantly. At 30 DAS the seedling length was highestwith KCl 1% and stout plants were observed with those raised from the non-primed seeds and seeds primed withdistilled water for 24h. SVI was highest with the seeds primed with KCl 0.5% and distilled water 12h. At 45 DAS,the treatments using urea 5% and 10%, KNO3 3% and non-primed seeds have resulted in taller seedlings. Whereasnon treated seeds and seeds primed with distilled water for 12h had higher girth. Highest number of leaves wasobserved when priming the seeds with distilled water for 24h, Urea 10% and KNO3 3%. SVI was highest withtreatments of KNO3 3%, non-primed seeds, distilled water for 12h and urea 10%. Since seed priming with KNO33% resulted higher SVI, seedling length and increased number of leaves that could be recommended for obtaininggood quality rootstocks in cashew.